The Arabidopsis Elongator complex is required for nonhost resistance against the bacterial pathogens Xanthomonas citri subsp. citri and Pseudomonas syringae pv. phaseolicola NPS3121. Issue 3 (30th January 2017) - An, Chuanfu; Wang, Chenggang; Mou, Zhonglin
Summary: Although in recent years nonhost resistance has attracted considerable attention for its broad spectrum and durability, the genetic and mechanistic components of nonhost resistance have not been fully understood. We used molecular and histochemical approaches including quantitative PCR, chromatin immunoprecipitation, and 3, 3′‐diaminobenzidine and aniline blue staining. The evolutionarily conserved histone acetyltransferase complex Elongator was identified as a major component of nonhost resistance against Xanthomonas citri subsp. citri ( Xcc ) and Pseudomonas syringae pv. phaseolicola ( Psp ) NPS3121. Mutations in Elongator genes inhibit Xcc ‐, Psp NPS3121‐ and/or flg22‐induced defense responses including defense gene expression, callose deposition, and reactive oxygen species (ROS) and salicylic acid (SA) accumulation. Mutations in Elongator also attenuate the ROS–SA amplification loop. We show that suppressed ROS and SA accumulation in Elongator mutants is correlated with reduced expression of the Arabidopsis respiratory burst oxidase homologue AtrbohD and the SA biosynthesis gene ISOCHORISMATE SYNTHASE1 ( ICS1 ). Furthermore, we found that the Elongator subunit ELP2 is associated with the chromatin of AtrbohD and ICS1 and is required for maintaining basal histone H3 acetylation levels in these key defense genes. As both AtrbohD and ICS1 contribute to nonhost resistance against Xcc, our results reveal an epigenetic mechanism by which Elongator regulates nonhost resistance in Arabidopsis.